Nutritional and therapeutic effect of Moringa peregrina on lead and cadmium – induced toxicity in rats compared with EDTA - Feryal F. Hussein AL-Azawi (Tikrit Journal of Pure Science, 2023)
The study was investigated to determine the Therapeutic effect of Moring peregrina (Forssk) seed powder at dose of 75 /mg/kg Bw./day comparis to calcium Disodium Ethylene – Diamine Tetra-Actic Acid CaNa2 EDTA at adose of 75/mg/Kg Bw oral post exposed to lead acetate or cadmium ehloride at adose 50/mg/K Bw orally for 6 weeks. 40 male rats divided into 9 group: G1= no treatment , G2 and G3= treated with lead or cadmium , G4= exposed to lead acetate for 6ws then M. peregrina for 2ws , G5= exposed to cadmium for 6ws then M. Peregrina for 2ws , G6 and G7= exposed to lead or cadmium for 6ws then CaNa2 EDTA for 2ws , G8 and G9 = exposed to lead or cadmium for 6ws then M. peregrina + CaNa2 EDTA . Results showed significant decrease (P≤ 0.05) in weight gain of rat in (G2 , G3 , G6 , G7 , G8 , G9).a Significant decrease (G4 and G5) relative to no treated animals. The hematological parameters showed a significant decrease in hemoglobin Hb Red Blood Cells (RBC) , Packed Cell Volume (PCV), while significant increase in white Blood Cells (WBC) , mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH) and lymphocytes.